Histological Changes in the Broiler Embryonic Pipping Muscle Between Days 15 and 19 of Incubation - Pulikanti, R.; Peebles , E.D.; Sokale, A.O.; Maslin, W.R. (International Journal of Poultry Science, 2012)
Nutritional and metabolic changes in the avian pipping muscle have been discussed by previous researchers. However, there are no reports in the literature on the histology of the embryonic pipping muscle in modern broiler strains. Therefore, the current experiment was conducted to examine histological changes in the embryonic pipping muscle of a modern broiler strain between d 15 and 19 of incubation. Ross x Ross 708 broiler hatching eggs were incubated on 8 replicate tray levels of an incubator. On d 15 and 19 of incubation, 2 embryos per level were extracted and their head and neck portions were preserved. The tissues were processed and stained using standard histological techniques. Subsequently, longitudinal and transverse sections of the embryonic pipping muscles on each of those days were examined under 2x, 4x, 10x, 20x and 40x magnifications. In preparation for hatch between d 15 and 19 of incubation, muscle fiber thickness increased, suggesting protein accretion and nutrient accumulation in the individual muscle fibers. Intra-fascicular muscle fiber density decreased and the inter-fascicular spaces widened and were filled with more cellular and fluid components, suggesting the active and selective infiltration of lymph into the pipping muscle from the surrounding lymph glands. In addition, the inter-fascicular spaces were filled with more cellular debris, which may be a result of muscle cell degeneration, necrosis, or associated apoptotic changes in the actively growing pipping muscle. Results of the current experiment provide an insight into the morphological changes in the pipping muscle during embryogenesis in a modern broiler strain. These together with the other associated changes in the nutritional profiles and the proteome compositions of the pipping muscle, as previously reported from our laboratory, facilitate a more detailed and comprehensive understanding of the various orchestrated cellular, metabolic and physiological events that occur in the pipping muscle of a modern broiler strain during the later part of incubation as the embryo prepares for hatch.